2011
DOI: 10.1016/s2221-1691(11)60104-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum nitric oxide and malondialdehyde levels in patients with acute intestinal amebiasis

Abstract: These results suggest that oxidative and nitrosative stress may play a major role in tissue damage in acute intestinal amebiasis patients. Also these parameters can be used to supplement the conventional microscopic method for reliable diagnosis of intestinal amebiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The presence of NO was also evaluated in intestinal amebiasis; in these reports, a significant increase in the NO levels in patients with diarrhea was found compared with the control group. These results support that this oxidative molecule possesses a central role in the pathophysiological mechanisms underlying amebiasis (Pérez-Fuentes et al, 2000 ; Namiduru et al, 2011 ).…”
Section: Oxidative and Anti-oxidative Microenvironment In Amebiasissupporting
confidence: 76%
“…The presence of NO was also evaluated in intestinal amebiasis; in these reports, a significant increase in the NO levels in patients with diarrhea was found compared with the control group. These results support that this oxidative molecule possesses a central role in the pathophysiological mechanisms underlying amebiasis (Pérez-Fuentes et al, 2000 ; Namiduru et al, 2011 ).…”
Section: Oxidative and Anti-oxidative Microenvironment In Amebiasissupporting
confidence: 76%
“…It has been described that oxidative stress and the presence of free-radical activities in hosts colonized by parasites correlate with the production of specific metabolites, such as advanced oxidative protein product (AOPP) and malondialdehyde (MDA) ( 44 46 ). Previous studies have evaluated MDA levels among healthy individuals and people infected by Ascaris lumbricoides ( 45 ), Entamoeba histolytica , and Plasmodium vivax ( 44 ), and all revealed increased levels of MDA in the infected individuals, suggesting that oxidative stress acts as a mediator of tissue damage concurrent with different parasites.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that high levels of NO are also found in conditions such as HIE, thalassemia, sickle cell disease and amoebiasis enteritis. [20][21][22][23] A cohort study was conducted by Correia-Costa L et al on 313 obese children. They found that the level of biological markers for oxidative stress and NO increased in relation to fat accumulation, as well as an association between increased oxidative stress and increased levels of NO.…”
Section: Discussionmentioning
confidence: 99%